Smart flap of sternocleidomastoid muscle in anterior cervical spine surgery: Surgical anatomical dissection technique. Issue 3 (1st November 2019) - Cuzzocrea, Fabrizio; Ghiara, Matteo; Vanelli, Roberto; Medetti, Marta; Lombardini, Ambrogio Alberto; Benazzo, Francesco; Mauramati, Simone; Mossinelli, Chiara; Herman, Irene; Benazzo, Marco
Abstract: The use of sternocleidomastoid muscle flap has firstly been described in 1909. In spine surgery, it is usually reserved in the cases of revision after anterior cervical spine procedures. The aim of this article is to introduce its usage as prophylactic measure in cases at high risk of iatrogenic fistula formation. The procedure consists of three main steps: sternocleidomastoid isolation, flap design and harvesting, and flap fixation. The use of a surgical anchor allows a better adherence to the plate preventing hematoma formation. The use of SCM smart flap in primary anterior cervical spine surgery as a prophylactic method could be considered a safe and feasible procedure in patients with a high risk of iatrogenic fistulas.